High-Vacuum Drainage System in Percutaneous Image-Guided Thoracocentesis for Complex Pleural Effusions - Yap, Jiawei Alexander; Gummalla, Krishna Mohan; H'ng, Martin Weng Chin (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose Our retrospective study is aimed to analyze the efficacy and outcomes between high-vacuum suction drain (HVSD) over passive drainage in the setting of percutaneous image-guided thoracocentesis, with a secondary aim to determine if preprocedural computed tomography (CT) can aid decision-making.Methods Clinical and imaging details of patients using HVSD between November 2012 and October 2018, who had a preceding CT within a month before drainage, were collated. The control group was selected from patients who had thoracocentesis with passive drainage performed between November 2017 and October 2018. Cases where HVSD was the sole device were compared with those using only a chest bottle.Results The HVSD was the only device in 17 cases compared to chest bottle in 47 cases. Mean duration being on a drain for these two arms were 5.5 and 7.3 days, respectively (p = 0.170). Fewer from the HVSD arm needed a repeat procedure (p = 0.424). Patients in the HVSD arm had significantly smaller volumes (p = 0.013) of higher density (p = 0.016), associated with a more encapsulating wall (p = 0.013) but not septations (p = 0.922). Density of contents on CT was useful in distinguishing between straw-colored effusion versus hemoserous fluid or pus (p = 0.008).Conclusions HVSD was not inferior to the chest bottle in the setting of thoracocentesis. Considering its potential adjunctive benefits, it should be an option for draining smaller volume complex effusions. Due to poor correlation with preprocedural CT, decision to insert a HVSD should be made by the procedurist at the time of thoracentesis.
Keywords: complex pleural effusions; high-vacuum; thoracocentesis